John’s prologue: Christological and doxological significance for the Johannine narrative - Hahn, Nathan; van Eck, Ernest (Pharos Journal of Theology, 2021)
This article presents a literary exegetical analysis of the prologue (John 1:1-18) of the Johannine narrative with special attention to the author’s (narrator’s) point of view. The author sets the tone of his gospel and writes with literary beauty while showing his theological points of view that will be seen throughout his narrative to follow. He presents Jesus as the eternal λόγος of God, and thus provides a unique point of view toward the Son of God of the Father who exists from eternity past with God the Father. Merely by studying, reflecting on, and remembering the Gospel’s prologue, the reader can understand and relate to the Christological and doxological significance of the Johannine narrative.